Improving Flywheel Stability through Finite Element Analysis - Iulian Stanasel; Florin Blaga; Caius Stanasel (Engineering Research: Perspectives on Recent Advances Vol. 2, 2025)
This paper presents a complex approach to the design and analysis of the drive flywheel for a monorail conveyor, covering the theoretical aspects of dimensioning calculations, 3D modeling, and the use of finite element analysis. Siemens NX software application integrates specialized software modules, including computer-aided design (CAD) and the finite element analysis (FEA) module, as well as engineering calculations, including optimization calculations. These tools allowed the simulation of flywheel performance under various operating conditions. After analyzing the initial results, a computer-aided optimization process focused on refining the flywheel geometry was implemented. This process involved the systematic adjustment of key geometric parameters, with the dual objective of minimizing the overall mass of the component and ensuring that internal displacements and stresses remain within allowable limits for safe operation. This iterative approach enabled the identification of a configuration that combines structural efficiency with functional performance. Integrating the three previously mentioned modules from the Siemens NX application allows both the automation of calculations and the significant acceleration of the development process, as well as an optimized constructive solution for the drive wheel. In addition, the ability to rapidly simulate and analyze multiple design variants substantially reduces the time and costs associated with physical prototyping and testing, facilitating a more efficient and agile development cycle for modern industrial products. Besides the practical aspect of the flywheel design, the article also presents the advantage of using software solutions with integrated CAD-FEA optimization modules, which can significantly reduce a product’s development time.